Promotion Strategy In increasing sales of Ivory Coast Palangkaraya Car Wash Services - MuhammadHasanGuzaiman; Rasyidi; SetioUtomo; Maryono (Magister Administrasi Bisnis ULM, 2024)
Abstract: This research approach uses an approach. Research informants, Ivory Coast Carwash admin owners and customers. Collecting data through observation, interviews and documentation. The results showed that the promotional strategy used to increase sales of Ivory Coast Car Wash services in Palangkaraya Public Relations Promotion method by providing good service, and also providing comfortable facilities for customers and meeting customer needs as desired. Personal Selling Method by offering existing services to Ivory Coast Carwash customers. The Sales Promotion method is through social media, especially through whatsapp and Instagram, starting from cooperation promotion updates, opening and closing hours and the process of working on services in Ivory Coast Carwash